Consumers Perception Under the Construct of Nationalism, Worldmindedness, “Made In” Label, and Brands - SUNARDI, GUIDO BENNY (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The implementation of economic integration under the ASEAN Community is accelerated to 2015. Many observers argued that Indonesian businesses were not ready to compete. Then, a study was conducted to examine how Jakarta consumers perceived the competitiveness of domestic shoes products, a leading Indonesian export products, against similar products made in some ASEAN and other developed and newly industrialized countries. The study employed six dimensions of Country Image for shoes products in revealing consumers’ perception of “made in” labels and consumers’ perception of brands. The study also adopted the constructs of consumers’ nationalism and worldmindedness. To increase the validity of the study, the respondents were carefully selected with judgemental quota sampling, using gender, area and cohort variables. The research revealed some interesting results that would be important for business people and government as regulator.